1978
DOI: 10.1577/1548-8659(1978)107<772:molass>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Landlocked Atlantic Salmon (Salmo salar) Hooked on Flies and Worms in a River Nursery Area

Abstract: To evaluate mortality of landlocked Atlantic salmon (Salmo salar) caught on flies and worms in a typical river nursery area, a study was carried out at the East Outlet of Moosehead Lake, Maine, in June 1975‐1977. Of 177 fish caught in the 3 yr, 22% died after hooking. All of the 74 control fish caught in a fishway trap survived. Mortality of worm‐hooked fish (35%) was significantly greater than that of fish hooked on flies (4%). Higher mortality of worm‐hooked fish was attributed largely to anatomical site of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 0 publications
2
38
2
Order By: Relevance
“…Schill (1996) reported that deep-hooking of rainbow trout (Onchorhyncus mykiss) was higher when fishing with slack line than when fishing with a tight line. Warner and Johnson (1978) found vastly different survival rates (0-100%) from different anglers, as a result of different deep-hooking rates. In that study the time allowed for a fish to swallow the bait varied across anglers, which probably affected the incidence of deep-hooking.…”
Section: Discussionmentioning
confidence: 99%
“…Schill (1996) reported that deep-hooking of rainbow trout (Onchorhyncus mykiss) was higher when fishing with slack line than when fishing with a tight line. Warner and Johnson (1978) found vastly different survival rates (0-100%) from different anglers, as a result of different deep-hooking rates. In that study the time allowed for a fish to swallow the bait varied across anglers, which probably affected the incidence of deep-hooking.…”
Section: Discussionmentioning
confidence: 99%
“…Rutledge (1975) concluded that mortality was not different among channel catfish of various size groups under 305 mm TL. In other studies, no correlation was established between hooking mortality and length in Atlantic salmon (Warner, 1978;Warner and Johnson, 1978), coho salmon (Lasater and Haw,I96I), rainbow trout (Dotson, 1982), cutthroat trout Dotson, 1982;Titus and Vanicek, 1988), largemouth bass (Rutledge, 1975;Rutledge and Pritchard, 1977;Pelzman, 1978;Schramm et al, 1987), striped bass, white bass, and palmetto bass (Childress, 1989a), and walleye (Goeman, 1991).…”
Section: A Length and Agementioning
confidence: 95%
“…Estimates obtained from landlocked populations were 8 to 18% in a lake (Warner, 1978), 3.3 to 5% in a hatchery (Warner, 1976(Warner, , 1979a, and 22% in a stream (Warner and Johnson, 1978). Mortality of chinook salmon (O. tsbawytschd) caught by trolling was estimated to be under 25% (Wertheimer, 1988;Wertheimer et al, 1989).…”
Section: Salmonidaementioning
confidence: 99%
“…Natural bait appears to increase the risk of deep hooking because fish are more likely to ingest natural bait and reject artificial lures or flies (May, 1973;Warner and Johnson, 1978;Diggles and Ernst, 1997). Cutting the line on deeply hooked fish significantly increased survivorship because attempting to retrieve deeply ingested hooks may cause further internal injuries.…”
Section: Release Mortality Factorsmentioning
confidence: 99%